IMPROVING FIFTH-GRADE STUDENTS' SCIENCE CONCEPT UNDERSTANDING USING A FLIPPED CLASSROOM WITH AUDIOVISUAL MEDIA - Alyada Ulya; Naffa Asti Aprilia; Agiska Cahnia; Andi Gusmaulia Eka Putri (PROGRES PENDIDIKAN, 2026)
This study examines the effectiveness of the flipped classroom model supported by audiovisual media in improving fifth-grade students’ understanding of science concepts at SD Negeri 182/I Hutan Lindung. Observations revealed that conventional lecture-based methods and minimal media use resulted in low student engagement, limited participation, and poor conceptual understanding. To address these challenges, Classroom Action Research (CAR) was conducted over two cycles, each including planning, implementation, observation, and reflection stages. During the planning phase, learning modules and audiovisual-oriented media were prepared in accordance with the Independent Curriculum. In the implementation phase, students studied material independently outside the classroom using digital media, allowing class time to focus on discussion, problem-solving, and concept reinforcement. Observations monitored student engagement and media effectiveness, while reflections informed iterative improvements. Quantitative analysis demonstrated that students’ average scores increased from 68 in the pre-cycle to 75 in cycle I and 85 in cycle II, with learning mastery rising from 40% to 90%. Qualitative findings indicated increased motivation, active participation, and collaborative interactions. The results confirm that integrating audiovisual media with a flipped classroom model enhances both engagement and conceptual understanding. This approach aligns with constructivist and multimedia learning theories, providing a practical solution to create more interactive, student-centered, and meaningful science learning experiences in elementary education.